IMPLEMENTASI NILAI PENDIDIKAN MULTIKULTURAL DALAM PAI - Annisa Nur Awaliyah Amri; Ali Muhtarom (QATHRUNÂ, 2021)
The purpose of the study was to describe the findings of multicultural education values ​​contained in the 2017 PAI & Budi Pekerti textbook for high school level which can be applied at SMK Negeri 12 Kab. Tangerang. The formulation of the problem of this research is whether there is the value of multicultural education in the 2017 PAI & Budi Pekerti textbook at the high school level, and how to apply the value of multicultural education in SMK Negeri 2 Kab. Tangerang. This research is a field research using a qualitative approach with a qualitative descriptive type of research. The data and data sources in this study were obtained from the 2017 Islamic Religion and Morals Education subject book at the high school level. The results of the study are expected to provide an understanding of the importance of inculcating the values ​​of multicultural education in the 2017 PAI textbooks at SMK N 12 Kab. Tangerang. The results of the study show that: 1) The multicultural values ​​developed in the book are the values ​​of democracy, tolerance, gender equality, and justice. 2) Implementation of PAI learning that is integrated with multicultural values ​​is carried out through the preparation of lesson plans, learning processes and learning evaluations. 3) The implementation of the values ​​of multicultural education in the learning carried out by the teacher has been adjusted to the lesson plan, the steps taken by the teacher in the implementation of learning are: the value of democracy, the value of tolerance, and the value of justice.